Evaluasi Kemampuan Shooting Cabang Olahraga Petanque Pada Atlet Rampagoe Petanque Club USK Tahun 2022 - Novi Lidya Isdarianti; Muhammad Jafar; Masri Masri; Agus Wiyanto (YLPK Mahardhika, 2022)
Petanque is a sport that is performed using an iron ball and a wooden ball as the basic means of playing. The basic petanque technique consists of pointing and shooting techniques. Shooting is a very important skill to win the game. The purpose of this study was to determine the level of shooting ability in the petanque sport of USK's Rampagoe Petanque Club athletes in 2022. Quantitative descriptive approach was applied. The research sample consisted of 30 athletes who were Rampagoe Petanque Club USK athletes. The data collection technique was carried out through a shooting ability test at a distance of 6.5 meters, 7.5 meters, 8.5 meters and 9.5 meters using different variations of iron balls. Each athlete has 3 chances to throw. Data analysis techniques are carried out by finding averages and percentages. The results of the data analysis carried out showed that the average shooting ability score was 45.7 (very poor) with the following details; 1) Very Good category with a frequency of 4 athletes (14%), 2) Good category with a frequency of 2 athletes (7%), 3) Moderate category with a frequency of 2 athletes (18%), 4) Poor category with a frequency of 3 athletes (10%), 5) very poor category with a frequency of 18 athletes (60%), Suggestions for the sport of petanque athletes rampagoe petanque club USK in 2022 so that athletes are more focused and concentrated in shooting because of their abilities shooting for the rampagoe petanque club USK athletes in 2022 is still in the Moderate category.